Dodgers Play Philadelphia Phillies at Dodger Stadium - Watkins, Howard::::::::: (1983)
Wide angle view of Dodger Stadium from behind home plate; Dodgers in field; pitcher in wind up Pitcher Alejandro Pena in motion